High‐Internal‐Phase Emulsion Tailoring Polymer Amphiphilicity towards an Efficient NIR‐Sensitive Bacteria Filter. Issue 37 (25th June 2015) - Huang, Xiaopeng; Yang, Youdi; Shi, Jiezhong; Ngo, Huynh Thien; Shen, Chaohua; Du, Wenbin; Wang, Yapei
<x xml:space="preserve">Abstract</x> Emulsions having a high internal‐phase volume fraction—termed as HIPEs for high internal phase emulsions—are in high demand as templates for functional macroporous materials. Designing molecular surfactants with appropriate amphiphilicity plays a critical role in the HIPE preparation. In this study, successful tailoring of the amphiphilicity of the originally hydrophobic block co‐polymer of polystyrene‐b‐polyvinylpyridine (PS‐b‐P4VP) is reported. In combination with trifluoroacetic acid, less than 5 wt% of the polymer–CF3COOH system is feasible as a surfactant for HIPE preparation; this is lower than the amounts typically needed for commonly used commercial surfactants. Using the HIPEs as templates, well‐defined closed‐ and open‐cell macroporous triacrylate‐based monoliths are fabricated simply through the adjustment of the ratio of the water phase to oil phase. After coating the resulting macroporous material with polypyrrole nanoparticles, the system can be exploited as an NIR‐sensitive filter for bacteria; it not only excludes oversized bacteria, but it also kills the bacteria with the help of NIR‐induced heat.